From Pots to Phones: A Study of Nomophobia among Catering Students - Zakariah , Siti Hajar; Hamdan, Nor Hidayah; Rosdi , Nur Danisyah; Tukiran, Nor Anis Intan Aqiah; Ahmad, Nor Aziah (Journal of Technical Education and Training, 2024)
In recent times, the passage of time has led to rapid technological development worldwide. Various gadgets, such as smartphones, tablets, and laptops, have emerged in tandem with the swift pace of technological advancement. Nomophobia is the fear and anxiety experienced by an individual in the absence of a cellphone or smartphone. This clearly indicates that gadgets fulfill various needs and hold significance in society. However, the issue of gadget addiction, better known as Nomophobia, also persists in conjunction with the rapidly growing technology among students. Therefore, the main objective of this study is to identify the factors causing Nomophobia and to assess the level of Nomophobia among students pursuing a Bachelor of Vocational Education (Catering) at UTHM. The methodology of this study involves a quantitative approach, using a survey method with a questionnaire distributed to respondents through the Google Forms platform. The results revealed that the mean value for all factors causing Nomophobia level is high. Additionally, the mean value for the level of Nomophobia among Catering students also indicates a high level of interpretation. Thus, this study suggests a need for enhancing future research to raise awareness among students about the adverse effects of Nomophobia. Additionally, this research hopes to serve as a guide for future researchers conducting studies in different areas.